On general axial gauges for QCD - Litim, Daniel F.; Pawlowski, Jan M. (Nuclear physics. Proceedings supplements, 1999)
General Axial Gauges within a perturbative approach to QCD are plagued by ‘spurious’ propagator singularities. Their regularisation has to face major conceptual and technical problems. We show that this obstacle is naturally absent within a Wilsonian or ‘Exact’ Renormalisation Group approach and explain why this is so. The axial gauge turns out to be a fixed point under the flow, and the universal 1-loop running of the gauge coupling is computed.